The Effectiveness of Problem Based Learning in Building Students' Character - Mega Nur Prabawati; Tatang Herman; Turmudi Turmudi (Pancaran Pendidikan, 2017)
Character building for the young generation nowadays is very urgent. It is because they see the phenomena that occur in the daily life of society and the challenges facing increasingly complex. Education implemented in schools not only provides the knowledge and skills that are academic only but can bring students to the next generation of the nation who not only have the skills of knowledge but also has a dignified character that can be reflected in the daily life of students. Education in schools through the activities of mathematical learning in the classroom should be well designed so that the purpose of shaping the character of students through learning of mathematics in school can be achieved. The purpose of building the character of the student is not easy, therefore a continuous and systematic plan is required. Lesson Design which contains the objectives of forming the character of the student should be seen, not just the impact of the accompanist of a learning plan only. One of the learning models that can build student character is problem-based learning. The character of the student can be built in each of the stages of problem-based learning include persistent, creative, tenacious, and curiosity.